Persuasion and Affect in the Framing of Poverty: An Experiment on Goal Framing - Abril, Eulàlia P.; Universidad de Illinois (2014)
In response to the vast and sometimes conceptually inconsistent literature on valence framing, Levin and colleagues (1998) advanced a typology of valence framing that organized the differing results by risky choice, attribute, and goal framing. This study furthers the literature on goal framing by (a) applying it to the context of a social issue, extreme child poverty; and (b) examining affective mechanisms under which goal framing is persuasive. Experimental results (N = 197) revealed that exposure to the loss-framed message led to greater willingness to support public policies to eradicate child poverty compared to the gain-framed message. Results also found evidence that negative affect served as the mediator of framing effects on public policy support. These findings suggest that, in the context of social support for aiding the poor, the persuasiveness of the loss frame is facilitated when participants experience negative, but not positive, affect.